Vaginal dysbiosis and the potential of vaginal microbiome-directed therapeutics - Valeriano, Valerie Diane; Lahtinen, Emilia; Hwang, In-Chan; Zhang, Yichan; Du, Juan; Schuppe-Koistinen, Ina (Frontiers in Microbiomes, 2024)
A healthy vaginal microbiome (VMB) is dominated by Lactobacillus spp. and provides the first line of defense against invading pathogens. Vaginal dysbiosis, characterized by the loss of Lactobacillus dominance and increase of microbial diversity, has been linked to an increased risk of adverse genital tract diseases, including bacterial vaginosis, aerobic vaginitis, vulvovaginal candidiasis, sexually transmitted infections, and pregnancy complications such as preterm birth. Currently, antibiotics and antifungals are recommended first-line treatments with high cure rates, but they also can lead to high recurrence and resistance development. As an alternative, lactobacilli have been utilized to restore the vaginal microbiota. In this review article, we discuss vaginal dysbiosis in various gynecological infections and potential interventions based on Live Biotherapeutic Products (LBPs) with a focus on those that use intravaginal treatment modalities to modulate the VMB. Based on these, we provide insights on key factors to consider in designing phenotypic and genotypic screens for selecting bacterial strains for use as vaginally administered microbiome-directed therapeutics. Lastly, to highlight current progress within this field, we provide an overview of LBPs currently being developed with published clinical trial completion for recurrent BV, VVC, and UTI. We also discuss regulatory challenges in the drug development process to harmonize future research efforts in VMB therapy.